Identification of Water Bacteria from Nickel Post Mining in East Halmahera - Margaretta, Margaretta Christita; Iwanuddin , Iwanuddin Iwanuddin; Yermias, Yermias Kafiar; Supratman , Supratman Tabba (Jurnal Wasian, 2018)
Nickel mining impact in heavy metal pollution on both soil and water. A method that is widely applied to reduce heavy metal contamination is bioremediation. Selection of bacteria that have potential reduction of heavy metal contamination in soil is very important in bioremediation process. The first step to select the potential bacteria is identification of samples. The purpose of this study is to identify existings bacteria in pond after nickel mining area PT. Antam, East Halmahera. Methods used in this research are isolation and identification of bacteria by conventional methods includes morphological, physiologica,l and biochemical test. Identification using Bergey’s Manual Determinative. The results showed there are 6 genera types of bacteria there are Bacillus, Esherichia, Enterococcus, Pseudomonas, Staphylococcus, dan Klebsiella, with 18 species in water of nickel post mining. Morphologically it is dominated by genus Bacillus as 50 % of the species. The identification of bacteria proved an existence of indigenous bacteria which is resistant to heavy metal stress.